2007
DOI: 10.1074/jbc.m700594200
|View full text |Cite
|
Sign up to set email alerts
|

Polarity of Response to Transforming Growth Factor-β1 in Proximal Tubular Epithelial Cells Is Regulated by β-Catenin

Abstract: Transforming growth factor-␤1 (TGF-␤1)-mediated loss of proximal tubular epithelial cell-cell interaction is regulated in a polarized fashion. The aim of this study was to further explore the polarity of the TGF-␤1 response and to determine the significance of R-Smad-␤-catenin association previously demonstrated to accompany adherens junction disassembly. Smad3 signaling response to TGF-␤1 was assessed by activity of the Smad3-responsive reporter gene construct (SBE) 4 -Lux and by immunoblotting for phospho-Sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
3
11
0
Order By: Relevance
“…Our current data demonstrated that inhibition of ß-catenin expression induced the expression of Smad3 protein, but reduced TERT protein expression. Another previous study presents similarity to our data such that the inhibition of ß-catenin augmented Smad3 signaling in proximal tubular epithelial cells (13). Smad3 has been know to block telomerase activation as shown in recent studies (38).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Our current data demonstrated that inhibition of ß-catenin expression induced the expression of Smad3 protein, but reduced TERT protein expression. Another previous study presents similarity to our data such that the inhibition of ß-catenin augmented Smad3 signaling in proximal tubular epithelial cells (13). Smad3 has been know to block telomerase activation as shown in recent studies (38).…”
Section: Discussionsupporting
confidence: 61%
“…Even so, recently, STAT3 is reported to be involved in the nuclear accumulation of ß-catenin in colorectal cancer (11), and Wnt/ ß-catenin pathway upregulated levels of STAT3 mRNA and protein in esophageal cancer cells (12). Smad3 signaling in proximal tubular epithelial cells is augmented by the inhibition of ß-catenin expression (13). ß-catenin expression is related to the upregulation of hTERT in gallbladder carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent reports have highlighted the complex, intertwined nature of the two signaling pathways [42]. Zhang and collaborators supported the hypothesis that b-catenin in renal epithelial cells, rather than in mesenchymal cells, may suppress TGF-b1-dependent signaling [43]. Furthermore, analysis of TGF-b1 transgenic mice showed reduced GS expression resulting from apoptosis of GS-positive hepatocytes [44].…”
Section: Discussionmentioning
confidence: 86%
“…33,34 Suppression of ␤-catenin promotes TGF-␤1-mediated proliferation of proximal tubular epithelial cells and colon carcinoma cells. 35 In this study, restoration of nuclear ␤-catenin abundance by recombinant Wnt3a protein and DKK1 siRNA attenuated the increase in expression of profibrotic factor induced by HG in mesangial cells, suggesting that impaired ␤-catenin signaling is one prominent pathologic reaction responsible for ECM metabolism in mesangial cells. Wnt4 promotion of ␤-catenin signaling participates in renal tissue development and HG-induced mesangial cell apoptosis.…”
Section: Treatment With Dkk1-as Alleviated Fibrosis In Renal Mesangiamentioning
confidence: 93%